Contested Spaces: The Communal Councils and Participatory Democracy in Chávez's Venezuela. (January 2017) - Wilde, Matt
Since their launch in 2006, the communal councils have been heralded as a significant step toward the establishment of a radical, participatory democracy in Venezuela. Ethnographic fieldwork carried out in a working-class barrio in Valencia, Venezuela's third-largest city, shows that local residents perceive and make use of the communal councils in a variety of ways. Older women in particular have become central players in community political life as a result of the reforms, although the burdens they take on arguably reproduce patterns of gendered inequality. Some residents express suspicion of new community leaders, accusing them of corruption, and there are conflicting views of what participatory democracy actually means in practical terms. The communal councils should be understood as contested spaces, the ambiguities and conflicts within them reflecting broader tensions within the Bolivarian project as a whole. Desde su lanzamiento en 2006, los consejos comunales han sido aclamados como un paso importante hacia el establecimiento de una democracia radical y participativa en Venezuela. Trabajo de campo etnográfico en un vecindario de clase trabajadora en Valencia, la tercera ciudad más grande de Venezuela, demuestra que los residentes locales perciben y hacen uso de los consejos comunitarios de muy diversas maneras. Las mujeres mayores, especialmente, han alcanzado un papel fundamental en la vida política de la comunidad como resultado de las reformas, aunque, podría decirse que las cargas que ellas asumen reproducen los patrones de la desigualdad de género. Algunos residentes tienen desconfianza de los nuevos líderes comunitarios y los acusan de corrupción. También, hay opiniones contrapuestas sobre lo que la democracia participativa en verdad significa en términos prácticos. Los consejos comunales deben entenderse como espacios en disputa y sus ambi-güedades y sus conflictos como reflejos de unas tensiones más amplias dentro del proyecto bolivariano en general.